Pelatihan Penerapan Program Statistical Product for Service Solution (SPSS) untuk Data Keolahragaan - Saharuddin Ita; Ibrahim Ibrahim; Miftah FP Putra (Jurnal Gema Ngabdi, 2020)
The dedication activity is expected to make participants (1) understand well about the SPSS program, and (2) can use the SPSS program to analyze the sports data (training results) that have been conducted. The results of the activities are (1) most of the trainees only know the SPSS program, (2) only a small number of participants can install the SPSS program independently, (3) most trainees understand well about the history and function of the SPSS, (4) some large participants can do descriptive analysis, test data requirements, correlation, t test (dependent and independent) independently, (5) only a small number of participants can do regression analysis and ANOVA.